Change and choice in Indian industry - Bagchi, Amiya Kumar(ed); Banerjee, Nirmala(ed) (Calcutta, 1981)
The book is the outgrowth of a seminar to which some of the most active economists in the field of industrial economics in India contributed. It ranges over both the general problems of India's industrial develop ment and factors constraining that development as well as specific problems relating to particular sectors such as steel production. It also covers policy issues such as the choice of technology or criteria for favouring small as against large-scale units. The book contains papers on the degree of concentration in Indian industry, problems of regulating monopoly power, and specific financial problems of both large and small-scale sectors. Among other policy matters discussed in the book are those of pro viding subsidies to exports and fiscal protection for indigenous technology. Besides the formal papers, the book is enriched and enlivened by the record of the informed discussion that took place around the papers presented.
Keywords: Industries India